2014
DOI: 10.1002/jcp.24706
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Sp1 to Telomerase Expression and Activity in Skin Keratinocytes Cultured With a Feeder Layer

Abstract: The growth of primary keratinocytes is improved by culturing them with a feeder layer. The aim of this study was to assess whether the feeder layer increases the lifespan of cultured epithelial cells by maintaining or improving telomerase activity and expression. The addition of an irradiated fibroblast feeder layer of either human or mouse origin (i3T3) helped maintain telomerase activity as well as expression of the transcription factor Sp1 in cultured keratinocytes. In contrast, senescence occurred earlier,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The herein used proliferative potential proxies should also be complemented with molecular biomarker expression analyses [15,17,18,32,33,34]. In light of our results, further characterization of the STAT-, p53-, AMPKα1-, and Akt-related signaling pathways in skin epithelial cell cultures is also needed.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The herein used proliferative potential proxies should also be complemented with molecular biomarker expression analyses [15,17,18,32,33,34]. In light of our results, further characterization of the STAT-, p53-, AMPKα1-, and Akt-related signaling pathways in skin epithelial cell cultures is also needed.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, it is generally preferred to use P1 to P3 keratinocytes when producing bio-engineered skin equivalents for clinical purposes [5,6,26]. Nevertheless, conducting these experiments into later passages could have yielded different results, as it has been shown that keratinocytes’ mean size, growth rate and key molecular processes can vary in later culture passages [15,18,27]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keratinocyte survival and expansion may be facilitated by growth‐arrested murine feeder layer fibroblasts (3T3 cells) which support keratinocyte attachment by synthesis of extracellular matrix proteins, release growth factors, remove toxic metabolites from culture media and delay primary keratinocyte terminal differentiation …”
Section: Introductionmentioning
confidence: 99%